Exposure to Neighborhood Violence and Child-Parent Conflict among a Longitudinal Sample of Dutch Adolescents - Jaap Nieuwenhuis; Matt Best; Matt Vogel; Maarten van Ham; Susan Branje; Wim Meeus (Institute of Labor Economics (IZA), 2021)
An extensive body of research has documented the deleterious effects of community violence on adolescent development and behavior. Much of this research focuses on how exposure violence structures social interaction, and, ultimately, how it motivates youth to engage in troublesome behavior. This study builds upon this body of research to demonstrate how exposure to community violence strains relationships between adolescents and their caregivers, resulting in higher levels of interpersonal conflict. Drawing on five waves of longitudinal panel data (n=778; observations=3,458; 55% female), combined with police records of violent crime in Utrecht, the Netherlands, a hybrid tobit regression documents how exposure to local and nearby violence affects child-parent conflict. The results indicate that youth who experience high levels of neighborhood violence report higher levels of conflict with parents than youth with low exposure to neighborhood violence. These results are consistent across different levels of neighborhood aggregation.
Keywords: I30; R23; 330; adolescent development; child-parent conflict; community violence; longitudinal panel